The Importance to Consider Advanced Fluid Properties in Flow Simulation of Positive Displacement Machines - Čelik, Anže (International Conference Fluid Power 2025: Conference Proceedings, 2025)
Simulation of positive displacement machines requires highly skilled engineers, use of advanced simulation tools and advanced simulation approach. The paper presents recent activities and progress on simulation of positive displacement machines – in particular, the axial piston pump and the radial hydraulic motor. Despite that these machines have been designed and produced for decades, there are still (design) features and phenomena not being investigated in detail or never being simulated. The simulation advancements mainly refer to the application of complicated kinematic motion, fluid properties, physics to consider as well as mesh and numerical algorithm techniques. In this paper, the focus is on modelling of advanced fluid material properties. Numerical approach has been performed by means of CFD within the environment of Siemens Simcenter Star-CCM+. The anticipation of cavitation has been possible by implementation of existing “full cavitation model”.